Determining transpiration efficiency of eight grain sorghum lines [Sorghum bicolor (L.) Moench] - Ayyaru Thevar, Prasanna (Kansas State University, 2008)
Transpiration efficiency (TE) is defined as total biomass produced per unit of water transpired. Improvement of TE means maximizing crop production per unit of water used. The objectives of the study were to examine, at the leaf level and the whole plant level, the variation in TE for sorghum [Sorghum bicolor (L.) Moench] accessions, previously screened for TE and to test physiological mechanisms that may account for differences in TE. Three field studies and two mini-lysimeter studies (one done in pots under greenhouse conditions and one done in pots in the field) were conducted with eight accessions. Instantaneous measurements of assimilation (A), stomatal conductance (gs), and transpiration by gas exchange provided measures of the transpiration efficiency at the leaf level. Growth observations and soil water balance in field plots quantified components of whole-plant TE. Growth and development measurements showed significant difference, explaining the existence of photoperiod sensitivity among the sorghum genotypes. Assimilation (A), stomatal conductance (gs), and maximum quantum efficiency of photosystem II (Fv/Fm) were consistently greater for accession PI533946 (from India) and greater for accession PI295121 (from Australia) in both field and the field-pot studies (p<0.05). Internal carbon dioxide (Ci), an indicator of intrinsic transpiration efficiency, differed among lines under field conditions (p<0.05). Leaf relative water content (RWC), measured in the greenhouse, and did not differ among the eight accessions. No consistent differences in biomass and water use were detected among lines under field conditions. In conclusion, developing reliable selection indices for TE will require a greater understanding of whole-plant physiological processes to utilize the differences in TE observed at the leaf level.
Keywords: Transpiration efficiency; Grain sorghum genotypes; Stomatal conductance; Internal carbon dioxide; Relative water content; Leaf gas exchange; Agriculture, Agronomy (0285); Agriculture, General (0473); Biology, Plant Physiology (0817)